Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Melalui Motivasi Pada Kantor Bawaslu Kabupaten Mamuju - Tamin, Tamin (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
This study aims at the impact of work discipline, job satisfaction on implementation through work motivation at the Bawaslu office, Mamuju Regency, West Sulawesi. This examination is directed to use a quantitative methodology which is expected to clarify the situation of the factors considered and the relationship between one variable and another. The population in this review is the Mamuju Bawaslu sample and 8 Panwascam in Mamuju District, up to 100 people. The testing test instrument used is an investigative method using the SmartPLS 3.2.9 program. The research results show that 1). Work discipline has a critical constructive outcome on representative practices. 2). Work motivation has important results that are useful in representative execution. 3) Fulfillment Work did not have a critical constructive outcome on . 4). Fulfillment work did not have major beneficial results on motivation. 5). Work motivation has very beneficial results in representative execution. 6). Work Discipline in MPerformance through worker motivation shows that work discipline has very beneficial results in implementation when interrupted by motivation. 7). Execution through motivation shows that work discipline has a positive and inconsequential impact on implementation every time it is intervened by inspiration at the Mamuju Bawaslu Office, West Sulawesi Region.